2012
DOI: 10.1103/physrevb.86.094303
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductance at the interface between crystals using equilibrium and nonequilibrium molecular dynamics

Abstract: In this article, we compare the results of non-equilibrium (NEMD) and equilibrium (EMD) molecular dynamics methods to compute the thermal conductance at the interface between solids. We propose to probe the thermal conductance using equilibrium simulations measuring the decay of the thermally induced energy fluctuations of each solid. We also show that NEMD and EMD give generally speaking inconsistent results for the thermal conductance: Green Kubo simulations probe the Landauer conductance between two solids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 45 publications
3
72
1
Order By: Relevance
“…Numerous MD studies showed that the temperature drops abruptly at the interface due to the phonon scattering and ITR. 7,[13][14][15] Meanwhile, it was additionally found that there are other temperature gradients at solid-solid interfaces. [10][11][12] These gradients are much steeper than those in the bulk solid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous MD studies showed that the temperature drops abruptly at the interface due to the phonon scattering and ITR. 7,[13][14][15] Meanwhile, it was additionally found that there are other temperature gradients at solid-solid interfaces. [10][11][12] These gradients are much steeper than those in the bulk solid.…”
Section: Introductionmentioning
confidence: 99%
“…MD simulation has been widely applied to investigate the thermal transport at GBs. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] By using MD simulation, it is possible to directly observe the independent molecular motion, which has so far been very difficult to obtain through experiments. In addition, the ITR can be interpreted by phonons, which are thermal energy carriers which play an important role when studying nanoscale heat transfer in a superlattice.…”
Section: Introductionmentioning
confidence: 99%
“…In order to confirm the results of the friction calculations with Eq. (1), and following a similar approach applied to the measure of thermal conductance, 55 we also estimated the friction coefficient using an alternative Green-Kubo formula involving the initial slope of the autocorrelation function of the slip velocity fluctuations at equilibrium, C vv = v slip (t)v slip (0) :…”
mentioning
confidence: 99%
“…On the other hand, MD simulations have been successfully used to directly calculate thermal boundary resistance [21][22][23][24][25][26][27] . These studies established the effects of sizes [28][29][30][31] , temperature 21,26,32 , mass differential of the two layers 21,26,27 , lattice mismatch between layers 26,27 , interfacial defects 26,27 , stiffness of the materials, and bond strength at the interface 22,24,32,33 . While the MD data provided knowledge significantly beyond that achieved from analytical models (e.g., the acoustic mismatch model and the diffuse mismatch model 2,9 ), our current understanding of the thermal boundary conduc-tance is far from the material/structure design requirement.…”
mentioning
confidence: 99%